Effect of dissolved organic matter on Fe(II) oxidation in natural and engineered waters. (15th October 2016) - Lee, Ying Ping; Fujii, Manabu; Terao, Koumei; Kikuchi, Tetsuro; Yoshimura, Chihiro
Abstract: Fe(II) oxidation was investigated in samples from the Sagami River basin (Japan) with particular emphasis on the effect of dissolved organic matter (DOM) in an urban river system. Collected samples consisted of main stream and tributary waters impacted to a moderate and minor extent by anthropogenic activities, respectively, and treated effluents from adjacent municipal wastewater treatment plants (MWWTPs: as representative anthropogenic point source). Nanomolar Fe(II) oxidation was measured in air-saturated waters using luminol chemiluminescence in the dark at 25 °C. Second-order rate constant for Fe(II) oxidation (with respect to Fe(II) and O2 concentrations) showed spatial and temporal variation. Annual average of the rate constant was highest for MWWTP effluents, followed by reservoir and river waters, with tributary waters showing the lowest oxidation rate. Manipulation experiments indicated that, in addition to pH (7.8–8.4), DOM characteristics are important explanatory variable for the Fe(II) oxidation. For example, the addition of MWWTP-derived humic-type DOM to anthropogenically less-influenced tributary water resulted in substantial increase in the oxidation rate. Significant negative correlation observed between the specific UV absorbance (SUVA254 ) and Fe(II) oxidation rate constant (pH 8.0) suggests a potential effect of humic-type DOM with low SUVA254 (high aliphatic content) on Fe(II) oxidation in natural and engineered waters. Graphical abstract: Highlights: Fe(II) oxidation was accelerated in the presence of MWWTP-derived DOM. SUVA254 had a significant negative correlation with Fe(II) oxidation. MWWTP-derived DOM had lower SUVA254 compared to riverine DOM. Iron transformation was substantially influenced by DOM quality and origin.